2013
DOI: 10.1021/jp4045308
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Transferability of the Sulfenyl Carbonyl Group −SC(O)– in Cyclic Thioesters

Abstract: The molecular and crystal structure of two dithiolactones (formally dimers of ε-caprothiolactone and ω-hexadecathiolactone) have been determined by X-ray diffraction at low temperature, revealing that the thioester group is planar with a synperiplanar orientation of the C═O double bond with respect to the S-C single bond. This conformational behavior is in contrast to that found for the smaller cyclic members of this family, where the antiperiplanar conformation is enforced. It is hypothesized that strain effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Although much less pronounced, also ɛ-TnCL shows a rise in ΔH p compared to ɛ-CL (Table 3, entries 11-12). The same trend was observed by Dugarte et al [104][105][106][107] and Suzuki et al [63] when calculating and comparing ring strain energies of lactones and thiolactones by means of DFT (Table 4). Both types exhibit the same trend of the ring strain energy significantly dropping from four to five-membered rings and subsequently increasing from five to seven-membered rings.…”
Section: Thermodynamicssupporting
confidence: 80%
“…Although much less pronounced, also ɛ-TnCL shows a rise in ΔH p compared to ɛ-CL (Table 3, entries 11-12). The same trend was observed by Dugarte et al [104][105][106][107] and Suzuki et al [63] when calculating and comparing ring strain energies of lactones and thiolactones by means of DFT (Table 4). Both types exhibit the same trend of the ring strain energy significantly dropping from four to five-membered rings and subsequently increasing from five to seven-membered rings.…”
Section: Thermodynamicssupporting
confidence: 80%
“…An example is given in Figure with the X-ray crystal structure of a thiodepsipeptide AIP-4 analogue. Thus, once thiolactones are sufficiently large and unstrained to enable both types of conformations, these structures preferentially adopt the syn conformation as in low molecular weight acyclic thioesters. …”
Section: Peptide Thioesters and Peptide Selenoesters: General Propert...mentioning
confidence: 99%
“…In this study, the calculated strain energy was observed to be 6.38 kcal/mol from MP2 calculations and 5.69 kcal/mol with the M06-2X functional. Several reports have pointed out that the strain energies of cyclic molecules are influenced by heteroatom substitution or functionalization. Thus, our results are comparable to these reports. The influence of substitution with the halogen atoms is quite minimal when compared to the heteroatom effect on the CHP ring.…”
Section: Results and Discussionmentioning
confidence: 96%